2003
DOI: 10.1007/s00428-003-0899-7
|View full text |Cite
|
Sign up to set email alerts
|

Difference in cytoplasmic localization pattern of neutral mucin among lobular endocervical glandular hyperplasia, adenoma malignum, and common adenocarcinoma of the uterine cervix

Abstract: To investigate whether the cytoplasmic localization pattern of neutral mucin differs between lobular endocervical glandular hyperplasia (LEGH) and cervical adenocarcinoma (CxAd), including minimal-deviation adenocarcinoma (MDA), or adenoma malignum, alcian blue (pH 2.5)/periodic acid-Schiff (AB-PAS) staining was performed to formalin-fixed paraffin-embedded tissue sections of 13 lesions of LEGH and 53 tumors of CxAd, including 6 tumors of MDA. The cytoplasmic localization of neutral mucin was classified as a "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Diffuse immunopositivities of HIK1083 and predominantly periodic acid-Schiff-positive neutral mucin expression were recognized in the glands of the lobular endocervical glandular hyperplasia, corresponding with the observations of previous investigators. 29,33,34 HIK1083-positive pyloric gland mucin was focally evident in three of four adenocarcinomas. This common expression of pyloric gland mucin in both lobular endocervical glandular hyperplasia and mucinous endocervical adenocarcinomas suggests the possibility that there is a histogenetical relationship between these two lesions.…”
Section: Endocervical Adenocarcinoma With Hyperplasiamentioning
confidence: 87%
See 2 more Smart Citations
“…Diffuse immunopositivities of HIK1083 and predominantly periodic acid-Schiff-positive neutral mucin expression were recognized in the glands of the lobular endocervical glandular hyperplasia, corresponding with the observations of previous investigators. 29,33,34 HIK1083-positive pyloric gland mucin was focally evident in three of four adenocarcinomas. This common expression of pyloric gland mucin in both lobular endocervical glandular hyperplasia and mucinous endocervical adenocarcinomas suggests the possibility that there is a histogenetical relationship between these two lesions.…”
Section: Endocervical Adenocarcinoma With Hyperplasiamentioning
confidence: 87%
“…27,29,30,[32][33][34]36 Because of the identical mucin expression in these lesions, several investigators have suggested that metaplastic or hyperplastic glandular lesions with pyloric gland mucin could be a precursor of minimal deviation adenocarcinoma. 32,34,37 Pyloric gland metaplasia also has been described in several other organs such as the pancreas, the gallbladder and the small and large intestine.…”
Section: Endocervical Adenocarcinoma With Hyperplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse and reddish cytoplasmic staining occurs with the PAS reaction, indicating that the cells produce neutral mucin, whereas normal glands and common endocervical adenocarcinoma have bluish acidic mucin on alcian blue staining. 2,11 Conversely, some investigators have reported immunoreactivity for HIK1083, which reacts with pyloric gland mucin of the stomach. Thus, HIK1083 is considered to be a useful tool for the differentiation of gastric metaplasia/ LEGH, MDA from common cervical AC and other benign cervical lesions.…”
mentioning
confidence: 92%
“…Although most cases are found incidentally, some may exhibit clinical, radiologic, and pathologic features resembling those of MDA (27,28). Therefore, it is difficult to differentiate MDA from LEGH preoperatively or postoperatively by clinical, radiologic, and pathologic features (29). To the best of our knowledge, the HPV status in LEGH has not been reported.…”
mentioning
confidence: 95%